Grain size and metallic trace element contents in sediments of Kemaman Coast, Terengganu, Malaysia, South China Sea - Abdullah, Nor Antonina; Mohamad Shazili, Noor Azhar; Yaacob, Rosnan; Yunus, Kamaruzzaman (David Publishing, 2014)
A total of 43 sediment samples were collected at Kemaman coast, Terengganu, by using Smith McIntyre grab. These sediments were analyzed to determine the grain size, sediment texture and metallic trace elements. Lazer diffraction method using PSA (particle size analyzer) was used to determine the grain size and sediment texture. Teflon bomb was used to digest the sediments for metallic trace elements concentration. Results showed that the study area was dominated with sand particles (60.5%) followed by loamy sand (20.9%), sandy clay (16.3%) and silt loam (2.3%). On the other hand, the average concentrations of each metallic trace elements were 0.12 μg/g for Cd; 36.6 μg/g for Cr; 9.51 μg/g for Cu; 11.6 μg/g for N: 41.5 μg/g for Zn and 29.3 μg/g for Pb. Based on the results, it was found out that coarse sediments showed lower levels of metallic trace elements and higher levels in fine sediments. In addition, enrichment factor was calculated to assess the pollution status of the study area. Based on the calculation, the enrichment of metallic trace elements ranked in the following order: Pb > Cd > Zn > Cu > Ni > Cr. The significant enrichment of Pb and moderate enrichment of Cd and Zn indicated that there are anthropogenic inputs while the rest of the metals can be considered from natural sources although there are effects of anthropogenic inputs in some sampling location.